2007
DOI: 10.1111/j.1742-1241.2007.01507.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the formation of small dense low-density lipoprotein particles in dependence on the presence of the metabolic syndrome and on the degree of glucose intolerance

Abstract: Our data point to different mechanisms of the formation of small dense LDL particles in dependence on the degree of glucose intolerance. Moreover, the target values for plasma TG should be set lower.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 41 publications
(45 reference statements)
2
14
0
4
Order By: Relevance
“…Using a different and more detailed methodology we here confirmed that small, dense LDL were reduced in our subjects with the metabolic syndrome and further showed that such reduction was confined in the LDL-IIIA, -IIIB and IVB subclasses. Previous studies suggested a central role of triglycerides in determining such levels of small, dense LDL [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a different and more detailed methodology we here confirmed that small, dense LDL were reduced in our subjects with the metabolic syndrome and further showed that such reduction was confined in the LDL-IIIA, -IIIB and IVB subclasses. Previous studies suggested a central role of triglycerides in determining such levels of small, dense LDL [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies [17][18][19] also suggested that small, dense LDL may represent a valuable marker for diagnosis and severity of the metabolic syndrome. Using the Lipoprint system Gazi et al [17] showed that subjects with the metabolic syndrome exhibit significantly higher concentrations of small, dense LDL than individuals who do not fulfill the criteria for such syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nos indivíduos com intolerância à glicose, o perfil lipídico geralmente encontra-se alterado e é caracterizado por aumento na concentração de VLDL (hipertrigliceridemia) e de apo B, baixas concentrações de HDL-C e, apesar do LDL-C ser normal ou discretamente elevado, há presença de LDL pequena e densa (FONTBONNE et al, 1989;GINSBERG, 1991;PIETZSCH et al, 1999b;TASKINEN, 2002;JULIUS et al, 2007a).…”
Section: A Importância Da Dislipidemia No Diabetes Mellitus E Na Intounclassified
“…O aumento na produção de VLDL 1 também contribui com a formação da LDL pequena e densa. A VLDL 1 é uma subclasse de VLDL maior e mais rica em triglicérides a qual, associada com a diminuição da ação da LLP no processo lipolítico, gera a fração de LDL pequena e densa enriquecida de triglicérides via CETP (PIETZSCH et al, 1999a;TASKINEN, 2002;PIETZSCH e FUECKER, 2003;ADIELS et al, 2005;JULIUS et al, 2007a).…”
Section: A Importância Da Dislipidemia No Diabetes Mellitus E Na Intounclassified